Public awareness of first aid treatment in acute burns - Kit Lum, Ho; Lam, U-Nee; Hn, Hidayah; Fernandez, Trevor A; Kuladeva, Dhanya; Farah, Nur Shazwani; Mohd Yussof, Shah Jumaat; Ibrahim, Salina (Journal of Surgery and Medicine, 2022)
Background/Aim: Burn injury is a global public health concern. First aid in burns can reduce morbidity and mortality by stopping the burning process and reducing the size and ultimate depth of the burn injury. The aim of this study is to assess the knowledge about first aid for burns in an urban population in Malaysia. Methods: We conducted a cross-sectional study using questionnaires to assess the knowledge about first aid for acute burns in our single tertiary main national referral unit for burn injuries. A total of 100 respondents were interviewed. Respondents were voluntary outpatients in the surgical outpatient department. Results: Twenty-two percent of the respondents complied with World Health Organization (WHO) recommendations. Other methods used were toothpaste (5.6%), soy sauce (4.4%), traditional oils (3.3%), aloe vera gels (2.2%), and a variety of creams (3.3%). Twenty-five percent agreed that the best information in first aid is through a first aid course; 15% chose a phone application, 14% chose a website, and 12% chose a television advertisement. The recommended first aid treatment (running tap water for ≥ 20 minutes) has proven beneficial in reducing tissue temperature and severity of injury. Conclusion: In 2019, 91% of the Malaysia population had access to the internet, which offers fast and reliable information on first aid for acute burn injuries. The majority of our population still lacks knowledge about first aid treatment for acute burns. Implementation of education regarding burn first aid should target all populations in Malaysia through different community health campaigns, with collaboration between government and non-governmental agencies.